2016
DOI: 10.1002/clc.22557
|View full text |Cite
|
Sign up to set email alerts
|

Admission Serum Calcium Levels Improve the GRACE Risk Score Prediction of Hospital Mortality in Patients With Acute Coronary Syndrome

Abstract: Background: The Global Registry of Acute Coronary Events (GRACE) risk score has been extensively validated to predict risk during hospitalization in patients with acute coronary syndrome (ACS). Recently, serum calcium has been suggested as an independent predictor for in-hospital mortality in patients with ST-segment elevation myocardial infarction; however, the relationship between the 2 has not been evaluated. Hypothesis: The combination of GRACE risk score and serum calcium could provide better performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…2 This last portion is strictly controlled by parathyroid hormone and vitamin D. 3 Total serum calcium concentration substantially varies on the serum concentration of albumin and hydration status without any alteration in the concentration of ionised calcium. [4][5][6][7] Hence, measuring only total serum calcium might be misleading. The gold standard for assessing calcium status is to measure ionised calcium.…”
Section: Introductionmentioning
confidence: 99%
“…2 This last portion is strictly controlled by parathyroid hormone and vitamin D. 3 Total serum calcium concentration substantially varies on the serum concentration of albumin and hydration status without any alteration in the concentration of ionised calcium. [4][5][6][7] Hence, measuring only total serum calcium might be misleading. The gold standard for assessing calcium status is to measure ionised calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Serum calcium levels are affected by several important factors including vitamin D and parathyroid hormone (PTH), serum phosphate, and magnesium levels [5,[8][9][10]. Abnormalities of calcium derangements and changes in serum calcium levels are common in clinical practice, especially among critically ill patients with prevalence up to 88% [5,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study suggest an increased risk of AKI not only in patients with elevated serum calcium ≥9.0 mg/dL, but also in those with reduced serum calcium ≤7.9 mg/dL on admission. Calcium plays a vital function in almost all biological processes including enzymatic activity, cardiac contraction and relaxation, and contraction of vascular smooth muscle[36][37][38][39] and studies have demonstrated associations of hypocalcaemia with poor left ventricular ejection fraction, 39-43 volume overload,44 and cardiac arrhythmias,40,41 which may result in AKI episodes. Although, in our sensitivity analysis of corrected serum calcium levels and risk of AKI, the association between decreased corrected serum calcium ≤7.9 mg/dL and risk of AKI was not statistically significant, this is likely because of underpower as there were only 133 patients with corrected serum calcium ≤7.9 mg/dL.There are several limitations in this study.…”
mentioning
confidence: 99%